Acute Toxicity Test of Bougainvillea glabra Choisy Leaf Extract Against Artemia salina Leach Larvae Using the Brine Shrimp Lethality Test Method - Nur Fadilla; Muhammad Asri SR; Nurfitria Junita; Suryanita Suryanita (Journal of Experimental and Clinical Pharmacy (JECP), 2026)
Bougainvillea plants are often referred to as paper flowers because the texture of the petals resembles paper. The leaves of this plant contain several metabolite compounds, such as alkaloids, flavonoids, saponins, and tannins, that have potential as anticancer. This study aims to determine the acute toxicity and LC50 value of paper flower leaf extract (Bougainvillea glabra Choisy) to shrimp larvae (Artemia salina Leach) using the Brine Shrimp Lethality Test (BSLT) method. This research method is experimental research with phytochemical screening testing and an acute toxicity test of B. glabra Choisy leaf extract against shrimp larvae (Artemia salina Leach) with the BSLT method. The results of this study showed that the phytochemical screening of B. glabra leaf extract contained alkaloid, flavonoid, saponin, and tannin compounds, with an LC50 value of 225.94 μg/mL. It is concluded that paper flower leaf extract has a toxic effect on Artemia salina Leach larvae because the LC50 value is 225.94 μg/mL with a moderate toxic category.